Perceptual image processing algorithm developing - Htoo, Maung Maung (2014)
Digital images have one of the most familiar things we interact in our daily life because we can take photos anywhere anytime with our personal mobile phone. Therefore, handling the digital images becomes popular. In the past decades, researchers have been developed various algorithms for image-related tasks but most of the algorithms still need the manual labor to accomplish the tasks.